Alcohol consumption, hypertension and obesity: Relationship patterns along different age groups in Uganda - Mbona Tumwesigye, Nazarius; Mutungi, Gerald; Bahendeka, Silver; Wesonga, Ronald; Katureebe, Agaba; Biribawa, Claire; Guwatudde, David (Preventive Medicine Reports, 2020)
The prevalence of non-communicable diseases including hypertension and obesity is rising and alcohol consumption is a predisposing factor. This study explored the effect of alcohol consumption patterns on the hypertension-age group and obesity-age group relationships. The data were extracted from the 2014 National NCD Survey of adults aged 18–69 years. Hypertension was defined as a condition of having systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg while obesity was defined as having a body mass index ≥30 kg/m2 . Frequent alcohol consumption was measured as alcohol use ≥3 times a week. Multivariable log binomial regression analysis was used to assess independent relationship between the outcomes and alcohol consumption. The prevalences of hypertension, frequent alcohol consumption and obesity increased across age groups but were divergent towards last age group. Hypertension prevalence ratios were higher with higher age groups among moderate and nondrinkers but not among frequent drinkers. Alcohol drinking pattern modified the age hypertension relationship in a model with ungrouped age. The drinking pattern did not modify obesity-age relationship. Alcohol consumption pattern appeared to modify the hypertension-age group relationship. However, more research is needed to explain why prevalence ratios are higher with higher age groups among moderate drinkers and abstainers while they stagnate among the frequent drinkers. There was no evidence to show the effect of alcohol consumption on obesity-age group relationship
Keywords: Hypertension; Obesity; Overweight; Non-communicable diseases; Alcohol Alcohol consumption; Alcohol epidemiology; Disease across age groups; Life span